Kepadatan Fitoplankton dan Larva Nyamuk Aedes albopictus pada Tempat Perindukan di Kecamatan Syiah Kuala Kota Banda Aceh - Sunarti Sunarti; Muhammad Ali; Mudatsir Mudatsir (Universitas Islam Negeri Ar-Raniry, 2018)
This study was conducted to determine the density index of phytoplankton and Aedes albopictus larvae found in breeding sites. The object of research was phytoplankton and Aedes albopictus larvae taken at Syiah Kuala District, Banda Aceh. Data was collected in December 2014 and January 2015. This study used a descriptive exploratory design. The research parameters are the type and density of phytoplankton found in various breeding places found at the study site. Data on the density of Aedes albopictus larvae was analyzed using the House and Container Index, and Density Index. This study found 15 species of phytoplankton with the larvae density index was 203 ind/L and phytoplankton density index was 649 ind/L.